A species interaction kick-starts ecological speciation in allopatry - Marius Roesti; Jeffrey S. Groh; Felicity C. Jones; Catherine L. Peichel; Dolph Schluter (Proceedings of the National Academy of Sciences, 2025)
Adaptation to different environments is thought to play a key role in speciation. However, speciation typically begins in allopatry, where reproductive isolation can also arise through neutral processes or selection unrelated to ecological differences. Disentangling the role of adaptive ecological divergence in the early stages of speciation therefore remains an important challenge in understanding the origin of new species. Here, we study threespine stickleback populations that have recently evolved in isolated postglacial lakes either in the presence or absence of prickly sculpin—a resource competitor that also shares ubiquitous trout predators with stickleback. We simulated secondary contact between several stickleback populations from these two ecological contexts in large, seminatural ponds, and genotyped offspring from 411 mating events to assess the strength of premating isolation associated with this biotic factor. Assortative mating between populations of the same ecological type (i.e., both sculpin-sympatric or both solitary) was moderate on average but ranged from weak to complete. Strikingly, and in line with a central premise of ecological speciation, the strength of premating isolation increased with increasing morphological and genomic population divergence shaped by sculpin-mediated selection. In contrast, overall phenotypic and genomic population divergence agnostic to sculpin presence/absence only poorly explained premating isolation, highlighting how ecological speciation in allopatry can be obscured by other sources of divergence. More broadly, our findings demonstrate how interactions with other ecologically similar species can play a major role in initiating and driving evolutionary trajectories toward new species, even in allopatry.